Hydrochemistry evolution in the shallow aquifer of Pulau Kapas, Terengganu, Malaysia - Mohd Isa, Noorain (2016)
Classified as a small island, Pulau Kapas, Terengganu, Malaysia has become renowned locations among tourists as it served clean beaches with attractive scenery, ocean activities and turtle hatching. In Malaysia, islands are one of the biggest contributors to ecotourism activities, which support the national economic growth and help to sustain Malaysia’s development. Apart from playing an important role in tourism, most of the small tropical islands faces similar problems regarding supplying freshwater. Due to the absence of surface water, small islands experiences major problems especially in supplying freshwater where groundwater abstraction is the only way to meet the demand of drinking water and domestic use. Higher demand of groundwater usage in the small island would possess a threat to the groundwater quality for example seawater intrusion and climate variation. The excess groundwater withdrawal may lead to vertical and lateral seawater intrusion. Meanwhile, climate variability is referring to low groundwater quantity due to dry season may eventually decreased its quality. Without proper planning and management, tourism could lead to degradation of an island environment. This study aimed to provide data on the temporal distribution of groundwater hydrochemistry in the small tropical islands and the important factors controlling the groundwater evolution as well as the spatial variation based on the study area characteristic. A total of 216 groundwater samples were collected during different monsoon of pre-, (dry season; August – October 2010) and post-monsoon, (wet season; February – April 2011) in six constructed monitoring boreholes (KW 1, KW 2, KW 3, KW 4, KW 5 and KW 6). Triplicate samples in each monitoring boreholes were analyzed including physicochemical parameter of in-situ and major ions as well as cation exchanges capacity analysis and heavy metals measurement. Based on ANOVA test, all of the parameters show significant effects (p < 0.01) with the changes of monsoon seasons. The groundwater hydrochemistry facies were displays as Na-rich with Na-HCO3 type during pre-monsoon while Ca-rich with Ca-HCO3 type during post-monsoon, respectively. Based on the environmental investigation via analytical analyses, the ionic ratios were used to distinguish the origin and chemical behavior of the groundwater where the groundwater was influenced by the cation exchanges processes, simple mixing and water-rock interaction. The saturation indices (SI) with respect to calcite and aragonite described that 76% of the groundwater samples were in under-saturation state (during pre-monsoon) while post-monsoon shows contrary results where most of the groundwater samples were under super-saturated condition. Additional of multivariate analyses of Principal Component Analysis (PCA) and Discriminant Analysis (DA) in present study can summarized the responsible factors controlling the groundwater evolution, which are the natural processes (ions exchanges process and saturation state of mineral) and human activities (over pumping which caused the up-coning of transition zone and simple mixing process). Meanwhile, the spatial variation was examined through the condition of groundwater in each monitoring boreholes using Hierarchy Cluster Analysis (HCA). There are two major groups which were classified as fresh groundwater (KW 3 and KW 4) and slightly affected/moderate condition of groundwater (KW 1, KW 2, KW 5 and KW 6). This classification was justified by the ionic strength calculation which reveals the same condition of groundwater in Pulau Kapas. The investigation of heavy metals concentration reveals the domination order of Sr > Fe > Mn > Al > Cr > Zn > Ni > As > Pb > Cu > Cd. None of these heavy metals exceeded the guidelines regulated by World Health Organization (2011) and Ministry Of Health (2012). Only Sr concentration was reported higher than permissible limits as this metal might abundance in the aquifer bedrock of study area. The cation exchange capacity (CEC) values shows a strong relationship with Ca concentrations, indicates the contribution of CaCO3 (aquifer bedrock) either by dissolution or precipitation state in determining the groundwater evolution. The structure and morphology of the sediment were explained by X-Ray Diffraction (XRD) test. Aragonite which has the highest percentage with 68% was the dominant mineral due to the deposition of corals. The existence of this mineral was confirmed by the Scanning Electron Microscopy - Energy Dispersive X-ray spectroscopy (SEM-EDX) data where the major elements were carbonate minerals (CaCO3). This study recommends an illustration on the complex system of groundwater aquifer as to reveal the groundwater hydrochemistry status and chemical mechanisms as well as the fingerprint of groundwater evolution in small tropical islands and specifically, Pulau Kapas. This study also offers a better understanding on groundwater hydrochemistry as it’s provide continuous data for future guidelines especially in the developing pristine environment.